Prosocial behaviors during school activities among child survivors after the 2011 earthquake and Tsunami in Japan: a retrospective observational study. - Masahide Usami; Yoshitaka Iwadare; Kyota Watanabe; Masaki Kodaira; Hirokage Ushijima; Tetsuya Tanaka; Maiko Harada; Hiromi Tanaka; Yoshinori Sasaki; Seiko Okamoto; Keisuke Sekine; Kazuhiko Saito (PLoS ONE, 2014)
Background The 2011 Japan massive tsunami traumatized many children. The aim of this study was to assess changes in strengths and difficulties experienced in home and school by among surviving children after the 2011 tsunami, in comparison with published normal Japanese data. Methods In November 2012 (20 months after the disaster) and September 2013 (30 months after the disaster), the Strengths and Difficulties Questionnaire (SDQ), a questionnaire on children's strengths and difficulties in home and school activities, were distributed to 12,193 and 11,819 children, respectively. An effective response of children 20 months and 30 month after the disaster was obtained in 10,597 children (86.9%), and 10,812 children (91.4%), respectively. The SDQ scores evaluated by parents and teachers were compared with published normal Japanese SDQ scores. Results The SDQ scores (emotional problems, conduct problems, hyperactivity/inattention, peer relationship problems, and total difficulty score) evaluated by parents of children in the 4th to 9th grade who were evaluated after 30 and 20 months were significantly high compared with the published normal data of children without traumatic experiences (all P<0.001). The SDQ scores (prosocial behavior) evaluated by teachers of children in the 4th to 9th grade who were evaluated after 30 and 20 months were significantly low compared with the published normal data of children without traumatic experiences (all P<0.001). Conclusions This study showed that the experience of the disaster affected those children with prosocial behaviors towards teachers and friends at school. However, no significant changes (in their prosocial attitude) had been seen at home, where they continued to keep their respect and caring feelings for parents. These results indicate that for accurate diagnosis, clinicians should not only evaluate these children's daily activities at home but also try to objectively assess their daily activities at school.